Improvement of sleep in patients with chronic idiopathic/spontaneous urticaria treated with omalizumab: results of three randomized, double-blind, placebo-controlled studies. Issue 1 (December 2016) - Gimenéz-Arnau, Ana; Spector, Sheldon; Antonova, Evgeniya; Trzaskoma, Benjamin; Rosén, Karin; Omachi, Theodore; Stull, Donald; Balp, Maria-Magdalena; Murphy, Thomas
Abstract Background Patients with chronic idiopathic/spontaneous urticaria (CIU/CSU) report difficulty with sleep. Methods We examined the effect of omalizumab on sleep-related outcomes during 3–6 months omalizumab or placebo treatment and a 16-week follow-up period within three Phase III double-blind randomized placebo-controlled pivotal trials in CIU/CSU: ASTERIA I, ASTERIA II, and GLACIAL. Sleep quality was assessed in all three studies using sleep-related questions included in an electronic diary, the Chronic Urticaria Quality of Life Questionnaire, and the Medical Outcomes Study Sleep Scale. Score changes from baseline in the treatment arms were compared with that in the placebo arm and adjusted for baseline score and weight. We also examined correlations of sleep scores at baseline, week 12, and week 24 and the slopes of change between sleep and itch and hive. Results Patients treated with omalizumab reported a larger reduction in sleep problems than those in the placebo arm; omalizumab 300 mg demonstrated the greatest improvement on all sleep components among all treatment arms. The largest reduction in sleep problems was reported within the first 4 weeks of therapy. After treatment discontinuation, sleep quality worsened. Sleep scores demonstrated moderate-to-strong correlation between them, and the change in sleep scores was associated with changes in itch and hives. Conclusions Improvement in sleep was reported after the first dose of omalizumab. Sleep continued to improve throughout the active treatment period. Patients receiving omalizumab 300 mg achieved greater improvement in sleep than those in other treatment arms. Trial registration ClinicalTrials.gov, NCT01287117 (ASTERIA I), NCT01292473 (ASTERIA II), and NCT01264939 (GLACIAL)